Students’ Perception of Online Learning Course of Speech and Arabic Debate during the COVID-19 Pandemic: Persepsi Pelajar Terhadap Pembelajaran Dalam Talian Kursus Pidato Dan Debat Arab Ketika Pandemik COVID-19 - Mohd Noor, Siti Salwa; Mohd Noor, Muaz; Mohammad, Tajulurrus (Jurnal Pendidikan Bitara UPSI, 2021)
The COVID-19 pandemic that hit the world starting in late 2019 has changed the country’s education system drastically and holistically. Learning and teaching previously implemented face -to -face is completely replaced by online learning mode through the use of various digital applications. This study aims to identify students’ perceptions of learning in Arabic speech and debate courses during the Covid-19 pandemic era. A total of 76 second year students of the Bachelor of Arabic, Sultan Zainal Abidin University (UniSZA), Terengganu were involved as respondents. This study uses a quantitative research method that is data collection through questionnaires distributed to respondents after the completion of the semester. There are 26 statement sentences in the questionnaire representing the respondents ’perceptions towards learning Arabic speech and debate courses online. A five -level scale was used to determine the level of respondents’ perception. The findings of the study were analyzed using descriptive analysis of mean and standard deviation. The results of the study found that students showed a positive perception of online learning while taking Arabic speech and debate courses. Therefore, educators should constantly improve the use of digital technology in teaching to ensure a conducive atmosphere in online learning classes. This aims to build a positive perception among students towards the world of digital education, especially in this era of the COVID-19 pandemic.